A Qualitative Analysis of Common Concerns about Challenges Facing Pharmacy Experiential Education Programs - Danielson, Jennifer (Am J Pharm Educ, 2015)
Objective. To qualitatively analyze free-text responses gathered as part of a previously published survey in order to systematically identify common concerns facing pharmacy experiential education (EE) programs. Methods. In 2011, EE directors at all 118 accredited pharmacy schools in the US were asked in a survey to describe the most pressing issues facing their programs. Investigators performed qualitative, thematic analysis of responses and compared results against demographic data (institution type, class size, number of practice sites, number and type of EE faculty member/staff). Expert and novice investigators identified common themes via an iterative process. To check validity, additional expert and novice reviewers independently coded responses. The Cohen kappa coefficient was calculated and showed good agreement between investigators and reviewers. Results. Seventy-eight responses were received (66% response rate) representing 75% of publicly funded institutions and 71% of schools with class sizes 51-150. Themes identified as common concerns were site capacity, workload/financial support, quality assurance, preceptor development, preceptor stipends, assessment, onboarding, and support/recognition from administration. Good agreement (mean percent agreement 93%, ƙ range=0.59-0.92) was found between investigators and reviewers. Conclusion. Site capacity for student placements continues to be the foremost concern for many experiential education programs. New concerns about preceptor development and procedures for placing and orienting students at individual practice sites (ie, “onboarding”) have emerged and must be addressed as new accreditation standards are implemented.